The transition of small-scale coffee farming systems and new pathways for coffee production: A case study in the central highlands of Vietnam - Thuy, Phan Thi; Niem, Le Duc; Lebailly, Philippe (Journal of Plantation Crops, 2022)
The dynamics of agriculture in general and coffee farming systems need to be investigated to derive insights for policies and interventions to promote sustainable agriculture. Through a systematic approach, including historical and adaptive ones, the study aims to probe the spatial-temporal transition of coffee farming systems. We found evidence for the diverse adaptive capacity of the coffee farming systems in Dak Lak province in their response to various factors. Moreover, an economic comparison was made between coffee farming systems, including mono-coffee farms and coffee-based intercropped ones. The study showed that coffee-based intercropped farms yield higher returns than mono-cropping ones by productivity enhancement, land equity ratio, and gross margin. These findings provided empirical evidence to design appropriate policies for the sustainable development of coffee farming.